Piloting and implementation of quality assessment and quality control procedures in RBC‐Omics: a large multi‐center study of red blood cell hemolysis during storage. Issue 1 (19th December 2018) - Stone, Mars; Keating, Sheila M.; Kanias, Tamir; Lanteri, Marion C.; Lebedeva, Mila; Sinchar, Derek; Hampton, Dylan; Jakub, Adam; Rychka, Val; Brewer, Greg; Bakkour, Sonia; Gefter, Nelly; et al.
Abstract : BACKGROUND: The major aims of the RBC‐Omics study were to evaluate the genomic and metabolomic determinants of spontaneous and stress‐induced hemolysis during RBC storage. This study was unique in scale and design to allow evaluation of RBC donations from a sufficient number of donors across the spectrum of race, ethnicity, sex, and donation intensity. Study procedures were carefully piloted, optimized, and controlled to enable high‐quality data collection. METHODS: The enrollment goal of 14, 000 RBC donors across four centers, with characterization of RBC hemolysis across two testing laboratories, required rigorous piloting and optimization and establishment of a quality assurance (QA) and quality control (QC) program. Optimization of WBC elution from leukoreduction (LR) filters, development and validation of small‐volume transfer bags, impact of manufacturing and sample‐handling procedures on hemolysis parameters, and testing consistency across laboratories and technicians and over time were part of this quality assurance/quality control program. RESULTS: LR filter elution procedures were optimized for obtaining DNA for analysis. Significant differences between standard and pediatric storage bags led to use of an alternative LR‐RBC transfer bag. The impact of sample preparation and freezing methods on metabolomics analyses was evaluated. Proficiency testing monitored and documented testing consistency across laboratories and technicians. CONCLUSION: Piloting and optimization, and establishment of a robust quality assurance/quality control program documented process consistency throughout the study and was essential in executing this large‐scale multicenter study. This program supports the validity of the RBC‐Omics study results and a sample repository that can be used in future studies.